Spatio-temporal assessment of nocturnal surface ozone in Malaysia - Yusoff, Mohd Famey; Latif, Mohd Talib; Juneng, Liew; Khan, Md Firoz; Ahamad, Fatimah; Chung, Jing Xiang; Mohtar, Anis Asma Ahmad (Elsevier, 2019)
This study aims to determine the level and potential sources of nocturnal surface ozone (NSO) in different regions in Malaysia. Eleven-year (2005–2015) ozone data from 37 continuous air quality monitoring stations throughout Malaysia have been analysed to determine spatio-temporal variations in NSO concentrations. NSO daily maximum concentrations from different regions in Malaysia were used for seasonal variation analysis while linear regression and the Mann-Kendall trend test were used for the annual variation analysis. Average ratios of mean NSO to daytime surface ozone (DSO) for the whole country were found to be 60% of DSO (0.58–0.61). The east coast of the Malaysian Peninsula recorded the highest ratio (70% of DSO) while the central region recorded the lowest concentration (50% of DSO). Titration processes, particularly by NO in the urban areas of the central region, and long transboundary movement of ozone to the east coast are expected to influence the concentration of ozone in these two regions, respectively. On certain occasions, the NSO concentrations (with a maximum value of 137 ppb) exceeded the limit of 100 ppb, the value suggested by Malaysian Air Quality Standard for ambient ozone concentration. The monthly diurnal variation analysis revealed the occurrence of secondary/nocturnal peaks at more than 50% of the stations occurring around 0300–0500 h. The NSO was found to be influenced by the monsoonal season with higher concentrations mainly observed during the boreal winter season. The long-term trend analysis presented the country's overall NSO as having an increasing trend at 27% of the stations.